Development of the Asia Pacific Lupus Collaboration cohort - Kandane‐Rathnayake, Rangi; Golder, Vera; Louthrenoo, Worawit; Luo, Shue Fen; Jan Wu, Yeong Jian; Li, Zhanguo; An, Yuan; Lateef, Aisha; Sockalingam, Sargunan; Navarra, Sandra V.; Zamora, Leonid; Hamijoyo, Laniyati; et al. (Wiley, 2019)
Aim: The aim of this manuscript is to describe the development of the Asia Pacific Lupus Collaboration (APLC) cohort. Method: The APLC cohort is an ongoing, prospective longitudinal cohort. Adult patients who meet either the American College of Rheumatology (ACR) Modified Classification Criteria for systemic lupus erythematosus (SLE), or the Systemic Lupus International Collaborating Clinics (SLICC) Classification Criteria, and provide informed consent are recruited into the cohort. Patients are routinely followed up at 3- to 6-monthly intervals. Information on demographics, clinical manifestations, treatment, pathology results, outcomes, and patient-reported quality of life (Short-form 36 version 2) are collected using a standardized case report form. Each site is responsible for obtaining local ethics and governance approval, patient recruitment, data collection, and data transfer into a centralized APLC database. Results: The latest APLC cohort comprises 2160 patients with >12 000 visits from Australia, China, Hong Kong, Indonesia, Japan, Malaysia, Philippines, Singapore, Taiwan and Thailand. The APLC has proposed the Lupus Low Disease Activity State (LLDAS) as a treat-to-target (T2T) endpoint, and reported several retrospective and cross-sectional analyses consistent with the validity of LLDAS. Longitudinal validation of LLDAS as a T2T endpoint is currently underway. Conclusion: The APLC cohort is one of the largest contemporary SLE patient cohorts in the world. It is the only cohort with substantial representation of Asian patients. This cohort represents a unique resource for future clinical research including evaluation of other endpoints and quality of care. © 2018 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd